DECOLONISING THE CURRICULUM AT CAMEROONIAN UNIVERSITIES: THE CASE OF THE DEPARTMENT OF EDUCATION FOUNDATION AND ADMINISTRATION - Ashu, Frederick Ebot (African Journal of Education and Practice, 2020)
Purpose: There is a consensus amongst social scientists and public administration practitioners about the importance of decolonising the curriculum at African universities, given that the Western model of academic organisation on which both the English and French Cameroonian university educational systems are based, remains largely unchallenged. Decolonisation involves removing the barriers that have silenced non-Western voices in our "˜multi-cultural' higher education system and combatting the epistemic injustices of a system dominated by Western thought. In this paper add to the conversation that the curriculum currently taught in Cameroonian universities does not meet the realities of the new Republic of Cameroon. This research was designed as a qualitative case study with the aim to investigates the process of decolonizing educational leadership and administration curriculum in Cameroonian universities preparing school leaders supporting quality education through effective leadership and administration. Methodology: To address this problem, this paper conducts two qualitative thematic reviews. The first is of the literature on decolonising curricula, with the aim of identifying a theoretical framework that can be applied to the specific context of the educational leadership and administration curriculum at the University of Buea in Cameroon, which is the focus of this study. These are Critical Decolonial Theoretical Framework (CDTF), and living theory methodology. It then further reviews the historical and contemporary curricula in Cameroon. Findings: The finding section shows how curricula were used by the colonial authorities to entrench coloniality and Western imperialism, and how globalisation serves to perpetuate those inequalities. Building on this understanding, it was evident that there was a dire need in Cameroon for a path towards the establishment of an indigenising curriculum, beyond the simple addition of indigenous local, national and international content. This paper was chosen as a case study since it offers the opportunity to embed the notion of decolonised curricula in the next generation of school leaders and educational scholars in Cameroon. Unique Contribution to Theory, Policy and Practice: The paper concludes with a case study proposing a decolonised educational administration and leadership curriculum at the department of Educational Foundations and Administration, Faculty of Education, University of Buea.